Istighotsah Rabu Pon sebagai Wahana Moderasi Beragama dan Multikulturalisme di Masyarakat Jawa Desa Sigayam - Aghitsny, Alaika; Majidah, Zahro Nur; Utami, Assyifa Dwi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Real Work Lecture (KKN) is a compulsory university program that aims to provide direct experience to students in community empowerment, as well as apply the theory obtained during lectures. In 2024, UIN Walisongo will hold a Religious Moderation KKN (KKN-MB) in Sigayam Village, Batang Regency, Central Java, which focuses on community service with the theme of religious moderation. The village is dominated by a Muslim community with a strong influence from the Nahdlatul Ulama organization, which supports routine religious activities such as tahlilan, yasinan, and Rabu Pon—a tradition based on the Javanese calendar to strengthen the harmony of the residents. Istighotsah Rabu Pon, a tradition that combines Islamic values and Javanese culture, reflects religious moderation. With the Javanese calendar inherited since the era of Sultan Agung, the residents of Sigayam Village continue to carry out this activity as a tribute to the traditions of their ancestors. This article explores the role of Istighotsah Rabu Pon as a bridge of local religious and cultural values, which helps maintain social harmony and cultural identity of the local community.